Perilaku Makan Siamang Dewasa (Hylobates syndactylus Raffles, 1821) Yang Hidup Di Hutan Terganggu Dan Tidak Terganggu - Abdul Rosyid (Universitas Tadulako, 2007)
The feeding behavior and of hylobates syndactylus (siamang) was investigated at the Way-Canguk Research area in Bukit-Barisan Selatan National Park between the months of February and July 2002. The research was conducted in undisturbed forest area (F1) and disturbed forest area (F2). Focal animal sampling method was use with and interval of 5 minutes. Six siamangs in each forest types were observed. The results of the investigations concluded that F1 and F2 siamangs spend more time resting than feeding. The percentage of feeding activity whichy is done by F1 and F2 Siamangs are 31% and 34%. The activity began at 6 until 7 am and increased to midday until 2 pm. After that, the activity decreased until 5.30 pm. The monthly range correlates negatively activity of F1 and F2 siamangs use mostly the middle layer of the canopy.